Extracellular-to-total body water ratio is associated with comorbidity and cardiorespiratory fitness in older adults with post-COVID-19 syndrome - Pleguezuelos, Eulogio; Del Carmen, Amin; Sánchez-Nuño, Sergio; Serra-Payá, Noemí; Moreno, Eva; Molina-Raya, Lorena; Jerez-Molina, Carmen; Girabent Farrés, Montserrat; Castizo-Olier, Jorge; Biurrun-Garrido, Ainoa; Viñals, Xavier; Serra-Prat, Mateu; et al. (Frontiers in Nutrition, 2026)
BackgroundPost-coronavirus disease 2019 (post-COVID-19) syndrome is associated with persistent impairments in physical fitness and altered body composition, particularly in older adults. The extracellular-to-total body water (ECW/TBW) ratio has been linked to poor outcomes in clinical populations. However, its association with cardiorespiratory fitness (CRF) and muscular fitness (MF) in older adults with post-COVID-19 syndrome remains unclear. This study aimed to examine the associations between ECW/TBW ratio, CRF, MF, and other variables in this population.MethodsA cross-sectional study was conducted in 71 older adults with post-COVID-19 syndrome. Hydration status and body composition were assessed using bioelectrical impedance analysis (BIA). CRF was evaluated by cardiopulmonary exercise testing (CPET; peak oxygen uptake, VO2peak), and MF was assessed using isokinetic and functional performance tests. Associations between ECW/TBW ratio, fitness outcomes, and other variables were analyzed through multi-variate linear regression models adjusted for age and sex. Results: Higher ECW/TBW ratio was significantly associated with lower VO2peak (β = −0.010, p = 0.048) and greater comorbidity burden (β = 0.003, p = 0.002). No significant associations were observed between ECW/TBW ratio and MF variables (p > 0.05).ConclusionsThe ECW/TBW ratio is independently associated with comorbidity burden and CRF, but not with MF, in older adults with post-COVID-19 syndrome. The Charlson Comorbidity Index emerged as the strongest determinant of ECW/TBW ratio. These findings highlight the potential relevance of integrating hydration monitoring and CRF assessment into rehabilitation strategies, and support further investigation of their role in the clinical management of older adults with post-COVID-19 syndrome.